2023
DOI: 10.1091/mbc.e21-03-0099
|View full text |Cite
|
Sign up to set email alerts
|

The scaffold RhoGAP protein ARHGAP8/BPGAP1 synchronizes Rac and Rho signaling to facilitate cell migration

Abstract: Rho GTPases regulate cell morphogenesis and motility under the tight control of guanine-nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs). However, the underlying mechanism(s) that coordinate their spatiotemporal activities, whether separately or together, remain unclear. We show that a pro-metastatic RhoGAP, ARHGAP8/BPGAP1, binds to inactive Rac1 and localizes to lamellipodia. BPGAP1 recruits the RacGEF Vav1 under EGF stimulation and activates Rac1, leading to polarized cell motility, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
(76 reference statements)
1
7
0
Order By: Relevance
“…Although the NP and PRR mutants also showed tendencies for lowered PSD95 content, only the PC mutant persistently produced significant effects (Fig 3L,Fig S2 B and C), indicating that the BCH domain could be crucial to the upkeep of synaptic protein content, balancing the effects of the GAP domain. This might reflect new evidence for ARHGAP8 found in the context of cancer cell movement, where the BCH domain is required to scaffold the activation of Rac1 by Vav in dependence of RhoA inactivation (Wong et al, 2023). Taken together, our results show that, while ARHGAP8-positive synapses were generally larger (Fig 1J), the overexpression of ARHGAP8 has the opposite effect on synapse size.…”
Section: High Levels Of Arhgap8 Destabilise Neuronal Morphologysupporting
confidence: 79%
See 1 more Smart Citation
“…Although the NP and PRR mutants also showed tendencies for lowered PSD95 content, only the PC mutant persistently produced significant effects (Fig 3L,Fig S2 B and C), indicating that the BCH domain could be crucial to the upkeep of synaptic protein content, balancing the effects of the GAP domain. This might reflect new evidence for ARHGAP8 found in the context of cancer cell movement, where the BCH domain is required to scaffold the activation of Rac1 by Vav in dependence of RhoA inactivation (Wong et al, 2023). Taken together, our results show that, while ARHGAP8-positive synapses were generally larger (Fig 1J), the overexpression of ARHGAP8 has the opposite effect on synapse size.…”
Section: High Levels Of Arhgap8 Destabilise Neuronal Morphologysupporting
confidence: 79%
“…Moreover, it is known that RhoGTPase regulators often contain multiple subdomains that allow for direct and indirect crosstalk between distinct RhoGTPase networks (Hodge & Ridley, 2016). New evidence emerged recently for ARHGAP8 concerting the inactivation of RhoA while also directing inactive Rac1 towards the RacGEF proteins Vav (Wong et al , 2023). Therefore, GluN2B might also control Cdc42 and Rac1 activity through ARHGAP8.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the binding of Cdc42 to α-Pix activates the GEF activity of α-Pix for Rac, and β-Pix (a Rac/Cdc42-GEF) forms a complex with srGAP1 (a RhoA-GAP) to regulate the activity of Rho GTPases (Baird et al ., 2005; Kutys and Yamada, 2014). Additionally, BPGAP, a GAP of RhoA, binds to Vav1 in lamellipodia, inactivates RhoA, and facilitates the GEF activity of Vav1 toward Rac, resulting in the promotion of lamellipodia formation (Wong et al ., 2023). Moreover, PLEKHG4B, which has a structure similar with Solo, binds to PDZ-RhoGEF and LARG and inhibits the activation of their GEF activities downstream of the G-protein coupled receptor (Muller et al ., 2020; Ninomiya et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“… 22 RhoGAPs have been shown to increase RhoGTPase activity and increase GTP hydrolysis. 4 Furthermore, RhoGAPs are commonly dysregulated in tumors. 22 , 23 ARHGAP30 is a RhoGAP that regulates Rac1 and RhoA activity.…”
Section: Discussionmentioning
confidence: 99%
“…Rho GTPases are GTP-binding proteins. 4 Recent studies have shown that Rho GTPases are overexpressed in many human cancers and are linked to tumorigenesis, invasion, and metastasis. 5 , 6 Rho GTPases bind with inactive GDP or with active GTP.…”
Section: Introductionmentioning
confidence: 99%